Facing up to the American dream: race, class, and the soul of the nation - Hochschild, Jennifer L. (Princeton studies in American politics : historical, international, and comparative perspectives, 1995)
What is the American dream? -- Rich and poor African Americans -- "What's all the fuss about?": Blacks' and Whites' beliefs about the American dream -- "Succeeding more" and "under the spell": affluent and poor Blacks' beleifs about the American dream -- Beliefs about one's own life -- Beliefs about others -- Competitive success and collective well-being -- Remaining under the spell -- With one part of themselves they actually believe -- Distorting the dream -- Breaking the spell -- The perversity of race and fluidity of values -- Comparing Blacks and White immigrants -- The future of the American dream